2002
DOI: 10.1124/jpet.300.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic Characterization of the Antipsychotic Drug Sertindole in a Rabbit Heart Model of Torsade de Pointes: Low Torsadogenic Potential Despite QT Prolongation

Abstract: There is growing concern that antipsychotic drugs that prolong the QT interval almost always increase the risk for patients to develop life-threatening ventricular tachyarrhythmias (VTs) of the torsade de pointes type. We therefore sought to compare the electrophysiologic effects of the psychotropic agent sertindole, which prolongs cardiac repolarization by inhibiting the rapid component of the delayed rectifier potassium current (I Kr ) but has a low torsadogenic potential to the antiarrhythmic agent dl-sotal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(30 citation statements)
references
References 36 publications
(35 reference statements)
6
22
0
2
Order By: Relevance
“…They showed a 15 to 17% prolongation of the QT interval at a perfusion concentration of 1.5 M sertindole without induction of TdP. In the present investigation in anesthetized dogs with normal hearts, 9% prolongation of the QT c interval was observed at 1.3 Ϯ 0.1 M. No TdP was observed, confirming the results from Eckardt et al (2002). Plasma protein binding in vivo and unknown levels of accumulation in cardiac tissue complicate comparisons between these models.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…They showed a 15 to 17% prolongation of the QT interval at a perfusion concentration of 1.5 M sertindole without induction of TdP. In the present investigation in anesthetized dogs with normal hearts, 9% prolongation of the QT c interval was observed at 1.3 Ϯ 0.1 M. No TdP was observed, confirming the results from Eckardt et al (2002). Plasma protein binding in vivo and unknown levels of accumulation in cardiac tissue complicate comparisons between these models.…”
Section: Discussionsupporting
confidence: 79%
“…Reported plasma concentrations from human volunteers receiving dofetilide ranged from 5 to 23 nM (Pfizer, 1999). Eckardt et al (2002) reported a low torsadogenic potential of sertindole in isolated rabbit hearts. They showed a 15 to 17% prolongation of the QT interval at a perfusion concentration of 1.5 M sertindole without induction of TdP.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this result was confirmed with studies on isolated tissues of feline and rabbit (Drici et al 1998;Eckardt et al 2002).…”
Section: Heterogeneous Chemical Classessupporting
confidence: 77%
“…Likewise, lidocaine could decrease significantly the incidence of TdP, but did so without affecting the QTc interval. These results corroborate earlier reports showing that QT prolongation did not correlate to the proarrhythmic liability of repolarization-prolonging drugs in isolated, AVablated rabbit hearts 66,67 .…”
Section: The Applied Repolarization Related Biomarkers Did Not Correlsupporting
confidence: 82%